2018
DOI: 10.1055/s-0038-1676502
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit Model of Extending Knee Joint Contracture: Progression of Joint Motion Restriction and Subsequent Joint Capsule Changes after Immobilization

Abstract: This study aimed to develop a rabbit model of knee contracture in extension and investigate the natural history of motion loss and time-dependent changes in the joint capsule after immobilization. We immobilized the unilateral knee joints of 32 rabbits by maintaining the knee joint in a plaster cast at full extension. Eight rabbits were euthanized at 2, 4, 6, and 8 weeks after casting, respectively, and the lower extremities were disarticulated at the hip joint. Eight control group rabbits that did not undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…In addition, we observed a high current flow (0.104 A ± 0.06), which is known to be associated with a cell proliferation effect 30,31 . This application could be interesting in more chronic phases in which the main objective is to improve the viscoelasticity of tissues, especially the capsule and ligaments, since, as reported in the literature, these structures are directly related to limitation of ROM after prolonged immobilization or chronic pathologies 17,18,25 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, we observed a high current flow (0.104 A ± 0.06), which is known to be associated with a cell proliferation effect 30,31 . This application could be interesting in more chronic phases in which the main objective is to improve the viscoelasticity of tissues, especially the capsule and ligaments, since, as reported in the literature, these structures are directly related to limitation of ROM after prolonged immobilization or chronic pathologies 17,18,25 .…”
Section: Discussionmentioning
confidence: 97%
“…Arthrogenic components, particularly of the joint capsule, are reported to be important factors in the formation of joint contractures. Previous studies have suggested that joint capsule fibrosis and overexpression of type I collagen occur and progress within 1 week after immobilization, and an increase in myofibroblasts is associated with this fibrosis 17 , especially in the posterior knee capsule 18 .…”
mentioning
confidence: 97%
“…Like our previous study, ROM of the left knee joint was measured by the joint motion measuring instrument. 11,12 According to the method described by Trudel G, 13…”
Section: Calculation Of the Total And The Myogenic Contracturementioning
confidence: 99%
“…It is widely accepted that in ammatory cytokines and pro brotic factors trigger the progression of brosis in the joint capsule and synovium [9][10][11]. Previous studies indicated that pro brotic growth factors are elevated during joint immobilization [12,13]. Of these, transforming growth factor-β (TGF-β), as a dominating pro brotic factor of arthro brosis, induces the plasticity and proliferation of broblasts with upregulated collagen in muscle contractures and other brotic tissues [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that pro brotic growth factors are elevated during joint immobilization [12,13]. Of these, transforming growth factor-β (TGF-β), as a dominating pro brotic factor of arthro brosis, induces the plasticity and proliferation of broblasts with upregulated collagen in muscle contractures and other brotic tissues [11][12][13]. Fibrous adhesion formation can be reduced by small proteoglycan, decorin, via the inhibition of TGF-β [14].…”
Section: Introductionmentioning
confidence: 99%